(untitled) (Revista História: Debates e Tendências, 2013)
Lately, globally-centered comparative histories have attracted considerable attention in the writing of environmen-tal history. To write such histories, however, it is necessary first to examine the role of regions, their development, and ultimately their global connections. Agricultural history is central to this discussion, including cattle ranching. Domestic animals have been an essential element in modern economic development, and yet erroneously livestock raising often has been seen as onedimensional, with little difference across regions and the world. By examining variation and ambiguity in southern Mato Grosso ranching the reader will come to better appreciate the complex historical relationship betwe-en environment, region and the world. Key words: Regions. Ranching. Envi-ronment. Mato Grossol.